Growth, Blood, and Intestinal Indices of Broilers at High Density Pens Provided with Fermented Averrhoa bilimbi Fruit Filtrate - Sugiharto, S.; Widiastuti, E.; Sartono, T.; Wahyuni, H.; Pratama, A.; Yudiarti, T. (Tropical Animal Science Journal, 2022)
The present study investigated the effect of fermented Averrhoa bilimbi fruit filtrate (FABFF) on growth, blood indices, and gut ecology of broilers raised at a high stocking density. Using 378 chicks (14 days of age), the study was arranged based on a factorial design with stocking densities (normal with 9 birds/m2 or high with 18 birds/m2) and treatment with 2% FABFF from drinking water or not as the two factors. Live body weight and feed consumption were registered weekly, while blood and intestinal contents were collected at day 35. Broilers at high density receiving FABFF had the lowest (p